2012
DOI: 10.1351/pac-con-11-07-15
|View full text |Cite
|
Sign up to set email alerts
|

Phosgene-free synthesis of 1,3-diphenylurea via catalyzed reductive carbonylation of nitrobenzene

Abstract: 1,3-Diphenylurea (DPU) has been proposed as a synthetic intermediate for phosgene-free synthesis of methyl N-phenylcarbamate and phenyl isocyanate, which are easily obtained from the urea by reaction with methanol. Such an alternative route to synthesis of carbamates and isocyanates necessitates an improved phosgene-free synthesis of the corresponding urea. In this work, it is reported that Pd(II)-diphosphine catalyzed reductive carbonylation of nitrobenzene in acetic acid (AcOH)-methanol proceeds in high yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 39 publications
3
17
0
Order By: Relevance
“…The reaction proceed smoothly giving high conversion and almost quantitative yield in about 20 h of reaction. Similar results were obtained by using CO as reductant in the presence of homogeneous Pd catalyst [20]. In Fig.…”
Section: Nitrobenzene Reductions With H(c=o)ona In Aqueous Biphasic Csupporting
confidence: 85%
See 2 more Smart Citations
“…The reaction proceed smoothly giving high conversion and almost quantitative yield in about 20 h of reaction. Similar results were obtained by using CO as reductant in the presence of homogeneous Pd catalyst [20]. In Fig.…”
Section: Nitrobenzene Reductions With H(c=o)ona In Aqueous Biphasic Csupporting
confidence: 85%
“…As a matter of fact, the reaction gives only 1-phenylethanol, and no traces of alcohol reduction. Despite of the presence of two liquid phase, reaction arrive to completeness in 20 h suggesting an activity of the catalyst comparable to those observed in the hydrogen transfer from NaOCHO nitrobenzene catalyzed by Pd catalyst, reported in the previous section, and also in reductive carbonylation of nitrobenzene with Pd catalyst [20]. Table 2 shows the activity of various catalyst in acetophenone reduction to 1-phenylethatol.…”
Section: Acetophenone Reduction With H(c=o)ona In Aqueous Biphasic Cosupporting
confidence: 72%
See 1 more Smart Citation
“…The removal of CO 2 molecule and further addition of CO transform intermediate ( III ) into ( IV ) which subsequently gave rise to intermediate ( V ) after the removal of CO 2 molecule. The addition of CO to ( V ) produced intermediate ( VI ) and also ( V ) in presence of water and CO (which is present in the reaction system) may procure corresponding amine ( VII ) , . The intermediate ( VI ) gave arylisocyanate ( VIII ) which may undergo hydration and subsequent formylation or following the transfer hydrogenation approach to give final product 2 and regenerating the Pd@PS catalyst ( I ) in the process (Scheme ).…”
Section: Optimization Studies For Pd@ps Catalyzed Synthesis Of N‐arylmentioning
confidence: 99%
“…The above differences in regioselectivity, reaction parameter effect, and substrate scope seem to indicate that the present selective carbonylations undergo different reaction pathways under Condition A and Condition B. It has been found that nitroarene can be catalytically reduced to nitrosoarene, aromatic amine, N-aryl hydroxylamine, and aryl isocyanate under CO atmosphere [16,17,[51][52][53]. Therefore, control reactions with these N-species would provide more insights into the present aminocarbonylation with nitroarene as N-source.…”
Section: Mechanistic Insightsmentioning
confidence: 99%